1969
DOI: 10.1172/jci106108
|View full text |Cite
|
Sign up to set email alerts
|

Organ culture of mucosal biopsies of human small intestine

Abstract: A B S T R A C T In vitro experiments of small intestinal mucosal function and metabolism utilizing excised tissue have been limited to a few hours by rapid epithelial cell necrosis which occurs with current incubation methods. We describe a method for culturing human mucosal biopsies for up to 24 hr employing organ culture methodology and demonstrate its potential application to studies of mucosal function. Peroral biopsies were placed in organ culture plates and maintained with modified Trowell's medium in 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
0
1

Year Published

1971
1971
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(138 citation statements)
references
References 20 publications
2
135
0
1
Order By: Relevance
“…Organ culture ofintestinal explants is a well-established technique for maintaining both adult (Browning & Trier, 1969) and foetal (Simon-Assmann et al, 1982) tissue for periods up to 48 h. We have previously adapted organ culture for pig small-intestinal explants and have shown that the morphology, at both the light-and the electron-microscopic level, is well preserved during culture up to 24 h (Danielsen et al, 1982a). The explants also maintained their contents of protein and microvillar enzymes and were able to sustain a continuous protein synthesis during the entire culture period.…”
Section: Resultsmentioning
confidence: 99%
“…Organ culture ofintestinal explants is a well-established technique for maintaining both adult (Browning & Trier, 1969) and foetal (Simon-Assmann et al, 1982) tissue for periods up to 48 h. We have previously adapted organ culture for pig small-intestinal explants and have shown that the morphology, at both the light-and the electron-microscopic level, is well preserved during culture up to 24 h (Danielsen et al, 1982a). The explants also maintained their contents of protein and microvillar enzymes and were able to sustain a continuous protein synthesis during the entire culture period.…”
Section: Resultsmentioning
confidence: 99%
“…Explants were cultured as described by Browning and Trier [29] with modifieations according to Naim et al [30] and Lottaz et al [31]. In brief, after 2 h in methionine-free medium explants were labelled continuously for 6 h with 150 ~tCi [~S]methionine (Amersham) in 1 ml medium.…”
Section: Organ Culture and Tmmwtoisolationmentioning
confidence: 99%
“…A ring of filter paper surrounding the central well was saturated with 150 mmol I -' NaCl and the culture dishes were placed in an incubator with humidified air, at 37 C . The organ culture technique followed that described and validated by Browning & Trier [14]. Control samples, boiled for 10 min in 150 mmol I -' NaCl were handled in a similar way.…”
Section: Methodsmentioning
confidence: 99%